Can you help me find my smile? - Sommer, Carl, 1930-; Budwine, Greg (Houston : Advance Pub., 1997)
Teddy, a bear who is constantly grumpy, discovers that the secret to being happy is helping others.
Keywords: Bears -- Fiction; Happiness -- Fiction; Conduct of life -- Fiction